The Impact of Family Communication and Spiritual Quotient on Student Self-Efficacy: Evidence from Islamic Junior High Schools - Sy. Nurul Syobah; A. Rivai Beta; Umair Tholib (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The transition from online to face-to-face learning in the post-pandemic era requires significant psychological adjustment for students. This study investigates the impact of Family Communication and Spiritual Quotient (SQ) on the Self-Efficacy of students at Islamic Junior High Schools (Madrasah) in East Kalimantan, Indonesia. Employing a quantitative approach with a correlational design, data were collected from 66 ninth-grade students selected through purposive sampling to represent the post-pandemic cohort. Validated questionnaires were used as instruments, and data were analyzed using Multiple Linear Regression. The results demonstrate that Family Communication (p=0.001) and Spiritual Quotient (p=0.015) significantly influence student self-efficacy, both partially and simultaneously. Notably, the regression model reveals that these variables collectively contribute 65% to students' academic confidence, indicating a strong predictive power. These findings suggest that the integration of open family communication and high spiritual intelligence serves as a critical psychological buffer against academic anxiety. This study implies that Islamic education stakeholders should prioritize spiritual-based parenting and communication strategies to enhance students' resilience and adaptability in the educational recovery era.